História do ensino da leitura no Espírito Santo (1946-1960) - Falcão, Elis Beatriz de Lima (2010)
This study investigates the teaching of reading in Espírito Santo primary schools, in the context of the first Brazilian Federal Government's primary education reform, implemented through the 1946 Organic Law of Primary Education (Decree-law no. 8.529, issued on January 2, 1946). We aim at understanding how Espírito Santo primary schools have employed the 1946 guidelines for teaching reading, between 1946 and 1960. We chose to study the teaching of reading in Espírito Santo in this period because it is a historical moment occurring between two primary education reforms: the Organic Law of Primary Education (Decree-law no. 8.529/1946) and the Brazilian Educational Guidelines and Bases Law (Law no. 4.024, issued on December 20, 1961). Making use of sources such as pedagogical meeting minutes, notes, newsletters, brochures, internal school documents, legislation, government announcements, printed press, and teaching programs we employed the Cultural History Approach by dialoguing with reflections of authors such as Chartier (1985) and Certeau (1994), especially those regarding the concepts of strategy, tactics, and representation. In this regard, the sources are conceived as discourses expressing representations of the employment of guidelines to teach reading which, through tactics or strategies, were put into practice in primary education in a particular historical context. We consider that the varied appropriation or use of these guidelines by the subjects in primary education contribute to highlighting that public policies have different shades within schools, either through resisting to what is new or through negotiating already consolidated practices